The Integrating technology into innovative learning environments to support mathematical knowledge, skills, and STEM learning - Rizki Sariningtias; Farida Nurhasanah; Getut Pramesti (Universitas Ahmad Dahlan, 2026)
This systematic literature review examines how technology is integrated into Innovative Learning Environments (ILEs) to support mathematical knowledge, skills, and STEM learning. Following the PRISMA guidelines, 22 studies published between 2013 and 2025 were selected from Scopus and Google Scholar. The review addressed six areas: research trends, definitions and characteristics of ILEs, forms of technology integration, types of mathematical knowledge and skills developed, contributions to 21st-century skills, and support for STEM integration. The findings indicate that Learning Management Systems, Virtual Learning Environments, interactive simulations, gamification, and Virtual Reality were among the most frequently reported technologies. Across the reviewed studies, these technologies were associated with the development of conceptual and procedural mathematical knowledge and the 4C skills of critical thinking, creativity, collaboration, and communication. Technology-enhanced ILEs also supported STEM integration through interdisciplinary and project-based activities connecting mathematical concepts with science, technology, and engineering contexts. However, the reported outcomes varied according to pedagogical design, teacher readiness, infrastructure, and local context. This review provides an integrated synthesis of the physical, pedagogical, social, and technological dimensions of ILEs and offers implications for the development of contextual technology- and STEM-integrated mathematics learning.